Sociomoral Reasoning in Adults with ADHD: A Pilot Study - Kate E. Thomason; Gisli Gudjonsson; Elaine German; Robin Morris; Susan Young (AIMS Press, 2014)
Attention Deficit Hyperactivity Disorder (ADHD) is frequently linked with antisocial behaviour, yet less is known about its relationship with sociomoral reasoning, and the possible mediating effect of intelligence. A pilot study was designed to investigate the relationship between antisocial personality traits, intelligence and sociomoral reasoning in adults with ADHD. Twenty two adults with ADHD and 21 healthy controls, matched for age, gender and IQ completed a battery of measures including the National Adult Reading Test, Gough Socialisation Scale and Sociomoral Reflection Measure-Short Form. There was no difference between the groups and levels of sociomoral reasoning, despite the ADHD group reporting greater antisocial personality traits. Sociomoral reasoning was positively correlated with intelligence. Results from a hierarchical multiple regressions indicated that both antisocial traits and IQ were significant predictors of sociomoral reasoning, with IQ proving the most powerful predictor. Whilst antisocial personality traits may explain some of the variance in levels of sociomoral reasoning, a diagnosis of ADHD does not appear to hinder the development of mature moral reasoning. Intellectual functioning appears to facilitate the development of sociomoral reasoning. A further analysis showed that both ADHD and low sociomoral reasoning were significant predictors of antisocial traits. The current findings have important treatment implications.